2018
DOI: 10.1080/0376835x.2018.1475219
|View full text |Cite
|
Sign up to set email alerts
|

Limited access to services for the urban poor in Windhoek, Namibia

Abstract: The majority of the population living in the informal settlements of Windhoek, Namibia, have limited access to public municipal services. This paper integrates results from a sample of 97 randomly selected households, interviews with experts and community leaders and review of literature to describe and analyze the relationship between land tenure and municipal services in the informal settlements. Findings from our study show that formalized land tenure is a condition for households to access municipal servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Between 2012 and 2016, an additional 15,000 shacks were built, i.e., around 3,500 new structures per year [49,50]. While most households have access to public piped water, accessibility to electricity, private toilets, and garbage removal is much more limited [51]. Formal unemployment in all three areas was close to 40% in 2011.…”
Section: Windhoek's Informal Settlementsmentioning
confidence: 99%
“…Between 2012 and 2016, an additional 15,000 shacks were built, i.e., around 3,500 new structures per year [49,50]. While most households have access to public piped water, accessibility to electricity, private toilets, and garbage removal is much more limited [51]. Formal unemployment in all three areas was close to 40% in 2011.…”
Section: Windhoek's Informal Settlementsmentioning
confidence: 99%
“…Research examining the disparity can be a consideration for the government to improve health facilities in rural areas. The government must be responsible for minimizing the disparity (Fu et al, 2018;Karuaihe and Wandschneider, 2018;Wong and Szeto, 2018;Li, Yao and Yin, 2018;Song, Shin and Kim, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This is because of the denser population density, so it is more profitable economically (Johar et al, 2018) (Dewi and Mukti, 2018). The government must be able to respond to this condition, it needs ongoing evaluation to ensure efforts to minimize the disparity between the two regions, and ensure better access in rural areas (Karuaihe and Wandschneider, 2018) (Dong, 2019) (Laksono, Wulandari and Soedirham, 2019a).…”
Section: Discussionmentioning
confidence: 99%
“…A study found that there are differences in health, access to and quality of healthcare between rural and urban areas in the United States (Anderson et al, 2015) (Zahnd and McLafferty, 2017) (Croft et al, 2018). Several studies in Africa and the European Union also revealed the same thing (Ravit et al, 2018) (Karuaihe and Wandschneider, 2018) (Piotrowska et al, 2018) (Yaya et al, 2019). Thus it can be concluded that the disparity in health services between urban and rural areas is still a global problem.…”
Section: Introductionmentioning
confidence: 99%